From an Ancient Road to a Cultural Route - Elifnaz Durusoy (Institut français d'études anatoliennes, 2014)
The main subject of the study is revealing "cultural routes", by the evaluation of ancient roads which have cultural accumulation on and around them. Considering the unique character of cultural routes, their formation as a consequence of cultural accumulation in a region is the main objective of the project. The project aims to explore the basic principles of cultural route planning and management in regard to the values of historic, natural, rural, modern and archeological components of cu...